PRODUKSI DAN KUALITAS JERAMI JAGUNG SEBAGAI PAKAN TERNAK SAPI DI KABUPATEN MINAHASA SELATAN - Paath, Ronald Hendro; Kaligis, David A.; Kaunang, Charles L. (Universitas Sam Ratulangi, 2012)
ABSTRACT The purpose of this study was to calculate the productivity of corn straw, and to measure the quality of corn straw as cattle feed at different altitude conditions, at South Minahasa regency. The research was conducted in May through September 2011, starting from collection of secondary data, primary data, on-site observations, corn straw sampling, and shipment of samples to be analyzed in Ruminant Animal Nutrition Laboratory and Livestock Chemistry, Faculty of Animal Science University of Padjadjaran Bandung. The results of the t-test analysis showed that there was a very significant difference between the protein, Neutral Detergent Fiber, Acid Detergent Fiber, and the production of corn straw in the lowlands and the highlands. Where in highlands, the production of corn straw and hay protein content was higher than in the lowlands, in lowland area was a reverse. A component of the Acid Detergent Fiber (ADF) and Neutral Detergent Fiber (NDF) was lower in the highlands than in lowlands. Corn straw can also be utilized as an animal feed based on Total Digestible Nutrient (TDN). Total Digestible Nutrient in West Amurang district was 2,204,785 kg (2,204.8 tons), while in Kumelembuai district, its was found only 877,533 kg (877.5 tons). It is concluded in this research that there were differences in the production of corn straw, protein, ADF, and NDF between lowland and upland areas. The protein content and the corn straw production as well as the content of ADF and NDF were higher in highland areas. Keywords : Corn straw, NDF, ADF ABSTRAK Tujuan penelitian untuk menghitung produktivitas jerami jagung dan tuntuk mengukur kualitas jerami jagung sebagai pakan ternak sapi pada kondisi ketinggian berbeda di Kabupaten Minahasa Selatan. Penelitian berlangsung sejak bulan Mei sampai dengan September 2011, mulai dari pengambilan data sekunder, data primer, pengamatan di lokasi, pengambilan sampel jerami jagung dan pengiriman sampel untuk dianalisis di Laboratorium Nutrisi Ternak Ruminansia dan Kimia Makanan Ternak Fakultas Peternakan Universitas Padjajaran Bandung. Hasil analisis uji t menunjukkan bahwa terdapat perbedaan yang sangat nyata protein, Neutral Detergent Fiber (NDF), Acid Detergent Fiber (ADF), dan produksi jerami jagung di dataran rendah dan dataran tinggi, di mana di daerah dataran tinggi produksi jerami jagung dan kandungan proteinnya lebih tinggi daripada di dataran rendah, tetapi untuk komponen ADF dan NDF lebih rendah di dataran tinggi daripada di daerah dataran rendah. Jerami jagung juga dapat memberikan kontribusi sebagai pakan ternak dilihat dari Total Digestible Nutrien (TDN) untuk Kecamatan Amurang Barat sebesar 2.204.785 kg (2,204.8 ton) TDN, sedangkan di Kecamatan Kumelembuai adalah sebesar 877.533 kg (877,5 ton) TDN. Hasil penelitian disimpulkan bahwa ada perbedaan produksi jerami jagung, kandungan protein, ADF, dan NDF antara daerah dataran rendah dan daerah dataran tinggi. Kandungan protein dan produksi jerami jagung lebih baik di dataran tinggi, sedangkan dilihat dari kandungan ADF dan NDF masih lebih baik di dataran rendah. Eugenia Volume 18 No. 1 April 2012 Kata kunci: Jerami jagung, NDF, ADF